White mineral trioxide aggregate mixed with calcium chloride dihydrate: chemical analysis and biological properties - Ahmed, Hany Mohamed Aly; Luddin, Norhayati; Kannan, Thirumulu Ponnuraj; Ahmad, Azlina; Mokhtar@Makhtar, Khairani Idah (The Korean Academy of Conservative Dentistry, 2017)
Objectives: This study aimed to evaluate the chemical and biological properties of fast-set white mineral trioxide aggregate (FS WMTA), which was WMTA combined with calcium chloride dihydrate (CaCl2·2H2O), compared to that of WMTA. Materials and Methods: Surface morphology, elemental, and phase analysis were examined using scanning electron microscope (SEM), energy dispersive X-ray microanalysis (EDX), and X-ray diffraction (XRD), respectively. The cytotoxicity and cell attachment properties were evaluated on human periodontal ligament fibroblasts (HPLFs) using methyl-thiazol-diphenyltetrazolium (MTT) assay and under SEM after 24 and 72 hours, respectively. Results: Results showed that the addition of CaCl2·2H2O to WMTA affected the surface morphology and chemical composition. Although FS WMTA exhibited a non-cytotoxic profile, the cell viability values of this combination were lesser than WMTA, and the difference was significant in 7 out of 10 concentrations at the 2 time intervals (p < 0.05). HPLFs adhered over the surface of WMTA and at the interface, after 24 hours of incubation. After 72 hours, there were increased numbers of HPLFs with prominent cytoplasmic processes. Similar findings were observed with FS WMTA, but the cells were not as confluent as with WMTA. Conclusions: The addition of CaCl2·2H2O to WMTA affected its chemical properties. The favorable biological profile of FS WMTA towards HPLFs may have a potential impact on its clinical application for repair of perforation defects.